PENINGKATAN KEMAMPUAN PENILAIAN PEMBELAJARAN GEOGRAFI - Mukminan, Mukminan; Suparmini, Suparmini; Nursa'ban, Muhammad (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2013)
The results of policy research in 2009 showed that geography teachers' understanding and skills in learning assessment still have not reached the standard. The purpose of this activity is the increased understanding of assessment techniques by geography teachers in Bantul with indicators of success at least 70% of participants obtain the results of the assessment in the category ofat least "good" and passed. The training method used theoretical and practical pragmatic thematic. Target Audience activity is geography teachers at the high school geography in Bantul as 41 people. The results: 1) only 35 participant (85.37%) passed with categories "Very good" 15 participant and 20 in "good" category. 2 there is an increased capability assessment techniques by geography teachers in Bantul was evidenced by the average pretest results of participants by 17% before training was conducting.Keywords: assessment, geography, teacher, and learning